The Implementation Of The Student Teams Achievement Divisions (STAD) Model To Improve Students Activeness In Social Studies Learning - Nurjannah, Utami (Metafora: Education, Social Sciences and Humanities Journal, 2019)
The background of this study is the low activeness students in Social Studies learning. This study aims to investigate the improvement of the activeness of Grade VIII A students of SMP Negeri 1 Duduksampeyan in Social Studies learning through the STAD model.This was a classroom action research (CAR) study. The research subjects were Grade VIII A students of SMP Negeri 1 Duduksampeyan in the academic year of 2019/2020 with a total of  32 students. The study was conducted in two cycles. Each cycle consisted of activity steps of planning, action and observation, and reflection. The data were collected through observations, interviews, field notes, and tests. They were analyzed by means of the qualitative technique using the interactive analysis model by Miles and Huberman consisting of data reduction, data display, and conclusion drawing. The data trustworthiness was enhanced through technique triangulation.The results of the study showed that the use of the STAD model was capable of improving the activeness of Grade VIII A students of SMP Negeri 1 Duduksampeyan in Social Studies learning. This was indicated by the improvement of each indicator for students’ activeness obtained from the data collected through observations, interviews, and field notes. In Cycle I, the results was still low so that the action was continued in Cycle II. In cycle II, the students’ activeness improved. The improvement from Cycle I to Cycle II satisfied the criterion for the success of the action, namely ≥ 75% so that the study was successful. Keywords : STAD, Students’ Activeness, Social Studies Learning